A Novel Stochastic Dynamic Modeling for PV Systems Considering Dust and Cleaning Effects - Cheema, Armaghan (2020)
A Master of Science thesis in Electrical Engineering by Armaghan Cheema entitled, “A Novel Stochastic Dynamic Modeling for PV Systems Considering Dust and Cleaning Effects”, submitted in November 2020. Thesis advisor is Dr. Mostafa Farouk Shaaban and thesis co-advisor is Dr. Mahmoud Hamed Ismail Ibrahim. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).